Radon exposure and potential health effects other than lung cancer: a systematic review and meta-analysis - Henyoh, Afi Mawulawoe Sylvie; Laurent, Olivier; Mandin, Corinne; Clero, Enora (Frontiers in Public Health, 2024)
Context and objective To date, lung cancer is the only well-established health effect associated with radon exposure in humans. To summarize available evidence on other potential health effects of radon exposure, we performed a comprehensive qualitative and quantitative synthesis of the available literature on radon exposure and health effects other than lung cancer, in both occupational and general populations. Method Eligible studies published from January 1990 to March 2023, in English and French languages, were identified in PubMed, ScienceDirect, Scopus, ScieLo and HAL. In the meta-analysis, we estimated average weighted standardized incidence ratios (metaSIR), standardized mortality ratios (metaSMR), and risk ratio (metaRR) per 100 unit (Bq/m3 or Working level Month) increase in radon exposure concentration by combining estimates from the eligible studies using the random-effect inverse variance method. DerSimonian & Laird estimator was used to estimate the between-study variance. For each health outcome, analyses were performed separately for mine workers, children, and adults in the general population. Results A total of 129 studies were included in the systematic review and 40 distinct studies in the meta-analysis. For most of these health outcomes, the results of the meta-analyses showed no statistically significant association, and heterogeneity was only present among occupational studies, especially between those included in the metaSIR or metaSMR analyses. However, the estimated exposure-risk associations were positive and close to the statistical significance threshold for: lymphohematological cancer incidence in children (metaRR = 1.01; 95%CI: 1.00–1.03; p = 0.08); malignant melanoma mortality among adults in the general population (metaRR = 1.10; 95%CI: 0.99–1.21; p = 0.07); liver cancer mortality among mine workers (metaRR = 1.04; 95%CI: 1.00–1.10; p = 0.06); intestine and rectal cancer mortality combined among mine workers (metaRR = 1.02; 95%CI: 1.00–1.04; p = 0.06). Conclusion Although none of the exposure-risk associations estimated in the meta-analyses reached statistical significance, the hypothesis that radon may have other health effects apart from lung cancer could not be ruled-out and call for additional research. Larger and well-designed studies are needed to further investigate this question. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023474542, ID: CRD42023474542.